The next frontier in healthcare: perspectives and discussion on building trust and societal acceptance of digital humans in the essential framework of impact biomechanics - Roth, Sebastien (Frontiers in Bioengineering and Biotechnology, 2025)
The digital twin: this term present in many scientific fields corresponds to a virtual model of a physical object. Used in several framework on the physics, the digital twin must be fidelic to reality, by closely reproducing the behavior and interaction with its environment. However, it is necessary, before using such a tool, to ensure that it is indeed realistic. In the context of impact biomechanics, one of the objectives of which is to understand the mechanisms of injury occurrence and the tolerance threshold, and ultimately to allow optimization of protective systems that would reduce the risk of injury occurrence, the concept of the digital twin relates to the development of a numerical model that must be biofidelic before it can be used for the development of protection systems. This paper raises the question of the biofidelity and the protecting ability of a digital twin and how one can trust the digital procedure to develop protecting devices, without data coming from physical procedures.